Impact of Non-Resident Fathers on The Social-Emotional and Moral Development of Children in Oyo Town - Gbemisola Olufunmilayo , Leye-Akinlabi; Aminat, Gbadegesin Motunrayo; Adedoyin Omowumi, Onafuye; Saheed Olawale, Olatunji (International Journal on Integrated Education, 2025)
This study investigated the impact of non-resident fathers on the social-emotional and moral development of children in Oyo town. Five specific purpose, five research questions and Bandura’s theory (1977) Social Learning Theory. Employing a qualitative research design, data were collected through semi-structured interviews with non-resident  fathers, single mothers, caregivers, and social workers. Content analysis was utilized to identify emergent themes from the collected data.​ Findings revealed that active involvement of non-resident fathers positively impacts children's emotional stability, self- esteem, and moral reasoning. Conversely, inconsistent or absent paternal engagement is associated with emotional withdrawal and behavioral challenges in children. Cultural norms, economic constraints, and societal expectations were identified as significant barriers to paternal involvement. Despite these challenges, some fathers employed strategies such as regular communication through phone calls and virtual interactions to maintain relationships with their children.​ The study concluded that non-resident fathers play a crucial role in their children's development. It recommends the implementation of supportive policies, community-based programs, public awareness campaigns, and educational resources to enhance non-resident fathers' capacity to contribute positively to their children's social-emotional and moral development.​